Original paperLong-term follow-up of percutaneous peripheral interventions in lower limb arteries in patients with acute coronary syndrome and diabetes - Bartuś, Stanisław; Siudak, Zbigniew; Chyrchel, Michał; Rakowski, Tomasz; Dziewierz, Artur; Brzeziński, Michał; Skowronek, Jacek; Bobrowska, Beata; Suska, Marcin; Dubiel, Jacek S.; Dudek, Dariusz (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2010)
Background : Diabetes mellitus is a quite frequent comorbidity among patients with acute coronary syndromes (ACS). The presence of diabetes has also predicted poor outcome after lower limb percutaneous transluminal angioplasty (PTA). Aim : To determine outcomes of patients with and without diabetes mellitus treated with PCI and PTA at index hospital stay during a 12-month follow-up. Material and methods : There were 116 NSTACS (non ST elevation acute coronary syndromes) patients gathered in this prospective registry study in 2003-2009 in one academic center in Krakow, Poland. Results : Data on consecutive patients who underwent PTA and PCI procedure during the same hospital stay were analyzed. Of these, 16 (14%) had diabetes mellitus, the other 100 (86%) had no history of diabetes. Both groups differed significantly with regard to gender and past medical history. During one-year observation 12.5% patients died in diabetes group vs. 2% in non-diabetes group (p = 0.033). Diabetes mellitus has turned out to be a strong predictor of outcome measured by the occurrence of repeated percutaneous peripheral procedure in 12-month observation. Conclusions : Patients with diabetes mellitus have more aggravating past medical history with more frequently coexisting comorbidities. Diabetes mellitus in patients with ACS treated by PCI and PTA is associated with impaired 1-year survival. Diabetes itself is a strong predictor of repeated PTA procedures.